GAMBARAN SISA MAKANAN PASIEN DI RSUD PETALA BUMI PROVINSI RIAU - Putri Lestari; Yessi Marlina (Poltekkes Kemenkes Mataram, 2021)
Background : The high amount of leftover food is a serious problem that must be addressed immediately because the food served in the hospital has taken into account the quantity and quality according to the patient's needs. This also indicates that nutrition services are not achieved. The purpose of this study was to describe the leftover in Petala Bumi Hospital, Riau Province by classifying based on meal time, treatment class, food texture and type of diet. Research Methods : The study used cross sectional design. The population of this study were all patients in room 1 stclass, 2nd class and 3rd class with a total sample of 8 people using purposive sampling method. The leftover was measured using a 6-point Comstock scale for 3 days including breakfast, lunch, dinner, morning and evening snacks. Research Result : The results showed that leftover was mostly found in animal side dishes of the lunch menu (87,5%), blenderized food in first class (100%0, and low-salt and high-fiber diets (100%). Conclusion : The most leftovers are in blenderized foods and low-salt and high-fiber diets.